Measuring social capital in creative teams through sociometric sensors. (1st January 2012) - Gloor, Peter A.; Grippa, Francesca; Putzke, Johannes; Lassenius, Casper; Fuehres, Hauke; Fischbach, Kai; Schoder, Detlef
We describe the results of an experiment capturing the face-to-face 'honest signals' of knowledge workers through sociometric badges. We find that collective creativity of teams is a function of the aggregated social capital of members. The higher it is, the higher their creative output. We collected communication data of 14 graduate students and their instructor during a one-week seminar, comparing it against the creative output of their teamwork. As a second component of social capital we also measured the level of trust team members show to each other through surveys. We find that the more team members directly interact with each other face-to-face, and the more they trust other team members, the more creative and of higher quality the result of their teamwork is.